Impact of Board Composition on Bank Performance : Evidence from the Indian Banking Sector - Kumar Singh, Amit; Sardana, Varda; Singhania, Shubham; Vikram, Aditya; Kumar Attree, Arun (Prabandhan: Indian Journal of Management, 2022)
India has recently witnessed a set of banking frauds, pointing toward the possibility of loose corporate governance mechanisms in the banking sector. The present study aimed to evaluate the composition of the board of directors in terms of the corporate governance parameters to assess whether they impacted the performance of the listed Indian banks. The hypothesis for the same was formulated based on the agency and the resource dependency theory . The study made use of the 34 public as well as private sector banks listed on the Bombay Stock Exchange 500 for a period of 12 years (2010–2022). The analysis was conducted using the STAT A software’s fixed-effect panel data regression model. The results suggested that board size, percentage of women directors, and percentage of independent directors on the board of banks impacted the financial performance of these banks. The study shed light on the mechanism and ways to improve bank performance using corporate governance parameters. It makes valuable contributions to the literature on corporate governance and shall be helpful for both managers and policymakers in formulating regulatory guidelines.